PENDAMPINGAN DIKLAT DAN SERTIFIKASI KOMPETENSI BAGI PENGURUS KOPERASI ERA DIGITAL DI KOTA SURAKARTA - Dina Damayanti; Rini Werdhiningsih; Retno Djohar Juliani; Firda Nisafera Ulfa; Muhammad Labib Khoirul Anwar; Salsabila Adivia (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2026)
Cooperatives play a strategic role in driving the local economy; however, they currently face challenges regarding digital transformation and the need for professional governance. This community service initiative in Surakarta City aims to enhance the capacity, professionalism, and readiness of cooperative administrators for competency certification, while also strengthening digital-based organizational management. The program integrates interactive education and training methods—including lectures, discussions, case studies, and simulations—with intensive support for competency certification, covering everything from portfolio preparation to assessment simulations. Results indicate a significant improvement in participants' understanding and skills regarding cooperative governance and risk management, as evidenced by pre-test and post-test evaluations. Furthermore, participants gained confidence in facing competency assessments and began adopting digital innovations, such as financial applications, administrative digitization, and social media utilization. In conclusion, the program proved effective in preparing cooperative administrators for certification and fostering digital transformation. To ensure sustainability, the implementation of a continuous post-certification program and expanded access to local government financing are recommended.